DERIVATISASI MORFIN MENGGUNAKAN DANSIL KLORIDA UNTUK MENINGKATKAN KEPEKAAN DETEKSI MORFIN PADA METODE KLT- SPEKTROFOTODENSITOMETER - Ari Chandrayan, L.P.; Linda L., N.P.; Widjaja, I.N.K. (Jurnal Farmasi Udayana; Vol. 1, No. 1, Tahun 2012)
Fluorescence detection could be used for enhance  the  sensitivity of morphine  detection  by TLC-Spectrophotodensytometry. Morfin is a compound  that fluoresces intrinsically incapable. ence, morphine  was derivatized using dansyl chloride. Morphine was derivatized by two methods, derivatization in solution and overspotting method. The derivatization reaction was kept at pH 9 and 450  C for 20 minute. The ratio between dansyl chloride and analyte concentration was 6:1. The derivatization result was separated from the interference using TLC. The TLC method was using Al-TLC silica G60 plate as a stationary phase and etyl acetate : methanol : amonia (85:10:5) as the mobile phase. The dansyl derivative was detected at ?eks 365 nm and K540 filter for fluoresence. Derivatization  of  morphine-dansyl chloride capable  to  enhancing  the  sensitivity of  morphine detection using TLC-Spectrophotodensytometry. Derivatization in solution and overspotting method took the same time in procedure  but  they  gave  different sensitivity. Derivatization in solution method gave more quantity  than derivatization of overspotting.
Keywords: morphine, dansyl chloride, derivatization, in solution, overspotting